Pengujian Blackbox Testing Sistem Informasi Booking Studio Musik Berbasis Web - Flavia Hana Alpriyan; Apriade Voutama (Journal of Students‘ Research in Computer Science, 2026)
Digital transformation in the creative industry sector demands the existence of integrated service systems capable of adapting to user needs. However, the music studio booking process that is still done manually often leads to various obstacles, such as scheduling problems, data recording errors, as well as inefficient administrative management. This condition suggests the need for a system that can manage the booking process in a more structured and computerized manner.This study focuses on the development of a web-based music studio booking information system aimed at improving service efficiency as well as facilitating schedule management. The development method used is a waterfall model that includes the stages of needs analysis, designing, implementation, and testing. System testing is carried out using the Black Box Testing method by evaluating the conformance between the input and the output generated. The results of the study show that the developed system is able to perform the main functions well according to the users’ needs. Thus, the system is expected to improve the service quality at music studio service providers.